Production and perception of emotional prosody by adults with autism spectrum disorder. Issue 12 (17th August 2017) - Hubbard, Daniel J.; Faso, Daniel J.; Assmann, Peter F.; Sasson, Noah J.
Abstract : This study examined production and perception of affective prosody by adults with autism spectrum disorder (ASD). Previous research has reported increased pitch variability in talkers with ASD compared to typically developing (TD) controls in grammatical speaking tasks (e.g., comparing interrogative vs. declarative sentences), but it is unclear whether this pattern extends to emotional speech. In this study, speech recordings in five emotion contexts (angry, happy, interested, sad, and neutral) were obtained from 15 adult males with ASD and 15 controls (Experiment 1), and were later presented to 52 listeners (22 with ASD) who were asked to identify the emotion expressed and rate the level of naturalness of the emotion in each recording (Experiment 2). Compared to the TD group, talkers with ASD produced phrases with greater intensity, longer durations, and increased pitch range for all emotions except neutral, suggesting that their greater pitch variability was specific to emotional contexts. When asked to identify emotion from speech, both groups of listeners were more accurate at identifying the emotion context from speech produced by ASD speakers compared to TD speakers, but rated ASD emotional speech as sounding less natural. Collectively, these results reveal differences in emotional speech production in talkers with ASD that provide an acoustic basis for reported perceptions of oddness in the speech presentation of adults with ASD. Autism Res 2017, 10: 1991–2001 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This study examined emotional speech communication produced and perceived by adults with autism spectrum disorder (ASD) and typically‐developing (TD) controls. Compared to the TD group, talkers with ASD produced emotional phrases that were louder, longer, and more variable in pitch. Both ASD and TD listeners were more accurate at identifying emotion in speech produced by ASD speakers compared to TD speakers, but rated ASD emotional speech as sounding less natural.